2015
DOI: 10.3390/bioengineering3010002
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing Redox to Improve Biobutanol Production by Clostridium tyrobutyricum

Abstract: Biobutanol is a sustainable green biofuel that can substitute for gasoline. Carbon flux has been redistributed in Clostridium tyrobutyricum via metabolic cell engineering to produce biobutanol. However, the lack of reducing power hampered the further improvement of butanol production. The objective of this study was to improve butanol production by rebalancing redox. Firstly, a metabolically-engineered mutant CTC-fdh-adhE2 was constructed by introducing heterologous formate dehydrogenase (fdh) and bifunctional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…To test this, we altered the cellular redox balance by adding formate to cultures or exposing cells to O 2 and studied their effects on transcription of adhA1 and adhA2 genes in C. beijerinckii. Supplementation of cultures with formate has been shown to provide a surplus of electrons for cells (23,24), whereas limited exposure to O 2 causes oxidative stress to clostridial cells (10,25). We observed that the transcript levels of adhA1 and adhA2 in the wild-type C. beijerinckii were significantly upregulated by formate supplementation and downregulated by limited exposure to O 2 ( Fig.…”
Section: Resultsmentioning
confidence: 66%
“…To test this, we altered the cellular redox balance by adding formate to cultures or exposing cells to O 2 and studied their effects on transcription of adhA1 and adhA2 genes in C. beijerinckii. Supplementation of cultures with formate has been shown to provide a surplus of electrons for cells (23,24), whereas limited exposure to O 2 causes oxidative stress to clostridial cells (10,25). We observed that the transcript levels of adhA1 and adhA2 in the wild-type C. beijerinckii were significantly upregulated by formate supplementation and downregulated by limited exposure to O 2 ( Fig.…”
Section: Resultsmentioning
confidence: 66%
“…As ethanol and n-butanol biosynthesis pathways are NAD(P)Hdependent, redox engineering has been applied to alter the electron flow to favor alcohols, instead of hydrogen, production in solventogenic clostridia (Cui et al, 2019;Lo et al, 2017;Ma et al, 2015b). Especially, ferredoxin NAD(P) + reductase has been overexpressed in C. acetobutylicum for increased butanol production (Bennett & Thakker, 2017;Qi et al, 2018).…”
Section: Effects Of Overexpressing Fnr On Fermentationmentioning
confidence: 99%
“…Therefore, various cofactor engineering strategies have been developed to regulate the redox balance and improve the yield and efficiency of microbial cell factories [108]. To maintain redox balance in the 1-butanol synthetic pathway, four strategies were employed, i.e., regulation of endogenous cofactor systems [37], heterologous cofactor regeneration systems [48], modifying cofactor preferences [60,109], and synthetic cofactor [32,49,110]. For example, endogenous cofactor regeneration strategy and acetyl-CoA were coupled as driving forces to direct the carbon flux in E. coli, through which 1-butanol production was improved to a level comparable to that produced by the Clostridium species, with a 1-butanol titer of 30 g/L and increasing the yield to 70% of the theoretical level [37].…”
Section: Cofactor Imbalancementioning
confidence: 99%